2009
DOI: 10.1037/a0013451
|View full text |Cite
|
Sign up to set email alerts
|

Healing the wounds of organizational injustice: Examining the benefits of expressive writing.

Abstract: Clinical and health psychology research has shown that expressive writing interventions-expressing one's experience through writing-can have physical and psychological benefits for individuals dealing with traumatic experiences. In the present study, the authors examined whether these benefits generalize to experiences of workplace injustice. Participants (N = 100) were randomly assigned to write on 4 consecutive days about (a) their emotions, (b) their thoughts, (c) both their emotions and their thoughts surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 80 publications
3
74
0
Order By: Relevance
“…Closure was assessed via LIWC indices of past, present, and future tense. These indicators have been employed broadly in previous narrative research (e.g., Pasupathi, 2007; Smyth & Pennebaker, 2008; Barclay & Skarlicki, 2009), and show good associations with observer-ratings (Francis & Pennebaker, 1997) as well as with contextual- and individual-difference factors (Pasupathi, 2007; Pennebaker & King, 1999; Pillemer, 2003). Preliminary analyses suggested that cognitive word use, a potential indicator of meaning-making, was uncorrelated with negative emotion and was not further examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Closure was assessed via LIWC indices of past, present, and future tense. These indicators have been employed broadly in previous narrative research (e.g., Pasupathi, 2007; Smyth & Pennebaker, 2008; Barclay & Skarlicki, 2009), and show good associations with observer-ratings (Francis & Pennebaker, 1997) as well as with contextual- and individual-difference factors (Pasupathi, 2007; Pennebaker & King, 1999; Pillemer, 2003). Preliminary analyses suggested that cognitive word use, a potential indicator of meaning-making, was uncorrelated with negative emotion and was not further examined.…”
Section: Methodsmentioning
confidence: 99%
“…However, though physical health and wellbeing may be related to emotion regulation, they are clearly distinct from it. Researchers have not examined whether expressive writing makes people less distressed about the issues they wrote about, and immediately after writing, people sometimes report greater distress (e.g., Murray & Segal, 1994) and other times reduced distress (Barclay & Skarlicki, 2009); it is not clear whether expressive writing would be related to less distress when people are reminded of the events they wrote about. More generally, expressive writing has never been compared to other emotion regulation strategies.…”
Section: Narrative As a Strategy For Emotion Regulationmentioning
confidence: 99%
“…The control participants, in direct contrast, write about a trivial topic. Typically, individuals who are writing about significant events report better psychological and physical health at the conclusion of the study than those in the control group (Barclay and Skarlicki 2009). Expressive writing can be a powerful tool in countering inhibition/avoidance and encouraging emotional processing (Wong and Rochlen 2009).…”
mentioning
confidence: 96%
“…Expressive writing is a brief intervention that has been linked to a multitude of physical health and psychological well-being benefits such as improved immune response (Pennebaker, Kiecolt-Glaser, & Glaser, 1988), fewer medical center visits (Pennebaker, Colder, & Sharp, 1990; Stanton & Danoff-Burg, 2002), reduced physical symptoms(Greenberg, Wortman, & Stone, 1996; Lu & Stanton, 2010), decreased pain among chronic pelvic pain sufferers (Norman, Lumley, Dooley, & Diamond, 2004), greater well-being (Barclay & Skarlicki, 2009), and higher relationship satisfaction (Baddeley & Pennebaker, 2011). In the traditional expressive writing paradigm, participants are instructed to reflect on a stressful experience and to write about their thoughts and feelings regarding that experience.…”
Section: Expressive Writing Interventionsmentioning
confidence: 99%